Adaptation of roots of several plants with Dictyosperma rubra Wendl. & Drude fruits found in the soil - Accorsi, Walter Radames; Barros, Myrthes A.S. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
It was verified phenotypic adaptation of roots of several plants (Paspalum notatum, Phyllanthus minuri, Solanum nigrum, Amaranthus sp, Cyperus rotundusand others) with fruits found in the soil of the palm-tree Dictyosperma rubra Wendl. & Drude cultivated as ornamental plant in the ESALQ park. This adaptation characterized by the penetration of roots through the round orifices found in the fruit pericarp promoted by an insect of the Bostriquide family and Coleoptera category. An experiment was realized in a plastic box with layers of soil alternated with layers of palm fruits without perforations. It was used the same weeds found near of the palm-tree in the park. It was verified after three months that the roots did not perforate the fruits, showed that the insects was not present in the soil.